Regulation of pharmaceutical prices: Evidence from a reference price reform in Denmark - Ulrich Kaiser; Susan J. Méndez; Thomas Rønde; Hannes Ullrich (Institute for the Study of Labor (IZA), 2013)
Reference prices constitute a main determinant of patient health care reimbursement in many countries. We study the effects of a change from an external (based on a basket of prices in other countries) to an internal (based on comparable domestic products) reference price system. We find that while our estimated consumer compensating variation is small, the reform led to substantial reductions in list and reference prices as well as co-payments, and to sizeable decreases in overall producer revenues, health care expenditures, and co-payments. These effects differ markedly between branded drugs, generics, and parallel imports with health care expenditures and producer revenues decreasing and co-payments increasing most for branded drugs. The reform also induced consumers to substitute from branded drugs - for which they have strong preferences - to generics and parallel imports. This substitution also explains the small increase in consumer welfare despite a substantial decrease in expenditures.
Keywords: I18; C23; 330; pharmaceutical markets; regulation; co-payments; reference pricing; welfare effects